2010
DOI: 10.1029/2010gl042558
|View full text |Cite
|
Sign up to set email alerts
|

Insights into processes and deposits of hazardous vulcanian explosions at Soufrière Hills Volcano during 2008 and 2009 (Montserrat, West Indies)

Abstract: International audienceDuring the Soufrière Hills eruption, vulcanian explosions have generally occurred 1) in episodic cycles; 2) isolated during pauses in extrusion, and 3) after major collapses of the dome. In a different eruptive context, significant vulcanian explosions occurred on 29 July 2008, 3 December 2008, and 3 January 2009. Deposits are pumiceous except for the 3 December event. We reconstructed the dispersal pattern of the deposits and their textural characteristics to evaluate erupted volume and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 20 publications
3
42
2
Order By: Relevance
“…We observed hydrous silicate minerals on erosional scarps of the dome complex, which would be consistent with water dissolving silica from dome rock and then cooling as it percolates out to the surface. The precipitation of siliceous sinter, in sufficient quantities, may have implications for dome stability and/or dome permeability (Boudon et al 1998;Komorowski et al 1997;Komorowski et al 2010). Based on our work, however, we cannot determine whether sinter at Santiaguito is sufficiently pervasive to have such effects.…”
Section: Discussioncontrasting
confidence: 45%
“…We observed hydrous silicate minerals on erosional scarps of the dome complex, which would be consistent with water dissolving silica from dome rock and then cooling as it percolates out to the surface. The precipitation of siliceous sinter, in sufficient quantities, may have implications for dome stability and/or dome permeability (Boudon et al 1998;Komorowski et al 1997;Komorowski et al 2010). Based on our work, however, we cannot determine whether sinter at Santiaguito is sufficiently pervasive to have such effects.…”
Section: Discussioncontrasting
confidence: 45%
“…For the 25 June 1997 SHV BAF described in detail by Loughlin et al (2002b), detachment of ash-cloud surges was found to occur at valley bends and constrictions, and was related to the slope of the channel, and was enhanced by depositional filling. Cole et al (2002), analysing data collated from 14 SHV flows, found Komorowski et al (2010). .…”
Section: Previous Workmentioning
confidence: 99%
“…A number of field studies investigate the morphology and granulometry of single events in great detail (e.g. Loughlin et al 2002b;Charbonnier & Gertisser 2008;Komorowski et al 2010;Lube et al 2011;Komorowski et al 2013), but few aggregate many events in order to extract general information and investigate similarities and differences between PDCs. Complex field relationships that result from the spatial and temporal variability of PDCs need to be reliably distilled in order to understand key physical processes which apply generically and which can be incorporated into dense-dilute coupled models.…”
mentioning
confidence: 99%
“…Pyroclastic density currents (PDCs) have deposited fine-grained, ash-and pumice-rich, and coarser-grained blocky deposits around the volcano (Cole et al, 2002;Stinton et al, 2014), supplemented by tephra deposits from short-lived Vulcanian explosions and associated fountain-collapse flows and surges (Komorowski et al, 2010). Prevailing winds often distribute ash from weak plumes to the west, but larger plumes can also deposit to the north, east and south (Bonadonna et al, 2002).…”
Section: Soufrière Hills Volcano Montserratmentioning
confidence: 99%
“…The andesitic dome-forming eruption of SHV began in July 1995 and has featured several phases of activity consisting of dome growth, dome collapse and Vulcanian explosions as well as pauses in magma extrusion (Bonadonna et al, 2002;Komorowski et al, 2010;Stinton et al, 2014). Pyroclastic density currents (PDCs) have deposited fine-grained, ash-and pumice-rich, and coarser-grained blocky deposits around the volcano (Cole et al, 2002;Stinton et al, 2014), supplemented by tephra deposits from short-lived Vulcanian explosions and associated fountain-collapse flows and surges (Komorowski et al, 2010).…”
Section: Soufrière Hills Volcano Montserratmentioning
confidence: 99%